2021
DOI: 10.3390/atmos12020209
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Climate Changes in Weddell Sea Region of Antarctica Detected by Extreme Values Theory

Abstract: On 13 February 2020, The Guardian, followed by many other newspapers and websites, published the news that on 9 February 2020, Antarctic air temperatures rose to about 20.75 ∘C in a base logged at Seymour Island. This value has not yet been validated by the WMO (World Meteorological Organization), but it is not the first time that an extreme temperature was registered in these locations. The recorded temperatures have often been described as “abnormal and anomalous”, according to a statement made by scientists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…A recent study has demonstrated that when the SAM-congruent trend is removed from the observed surface temperature trend, a background warming trend (consistent with the overall global warming) is observed over the past 60 years 13 , therefore linking regional mean AP warming with anthropogenic factors 33 . In agreement with the climate change signal detected herein for the 2020 AP heatwave event, long-term trends in warm extremes at Rothera and Halley stations have also been associated with accelerated regional warming 47 . The short record of observations, the large interannual to decadal variability of the AP region 14,48 and the multiplicity of drivers (e.g., SAM, the Amundsen Sea Low, El Niño Southern Oscillation (ENSO), sea ice variations; refs.…”
Section: Discussionsupporting
confidence: 88%
“…A recent study has demonstrated that when the SAM-congruent trend is removed from the observed surface temperature trend, a background warming trend (consistent with the overall global warming) is observed over the past 60 years 13 , therefore linking regional mean AP warming with anthropogenic factors 33 . In agreement with the climate change signal detected herein for the 2020 AP heatwave event, long-term trends in warm extremes at Rothera and Halley stations have also been associated with accelerated regional warming 47 . The short record of observations, the large interannual to decadal variability of the AP region 14,48 and the multiplicity of drivers (e.g., SAM, the Amundsen Sea Low, El Niño Southern Oscillation (ENSO), sea ice variations; refs.…”
Section: Discussionsupporting
confidence: 88%
“…Data from the permafrost station indicated instrumental problems, and consequently, the WMO accepted the value of 18.3°C at the Esperanza station as the highest temperature recorded in the Antarctic (Francelino et al 2021). Prete et al (2021) applied extreme value theory (EVT) to investigate annual maxima and minima in order to verify if temperatures recorded in February 2020 can be considered as usual or abnormal extreme events. The GEV were t to data from different Antarctic bases and used to project the 100-year return period.…”
Section: Introductionmentioning
confidence: 99%